Bacterial communities associated with white shrimp (Litopenaeus vannamei) larvae at early developmental stages - ARTINI PANGASTUTI; ANTONIUS SUWANTO; YULIN LESTARI; MAGGY TENNAWIJAYA SUHARTONO (Society for Indonesian Biodiversity, 2010)
Bacterial communities associated with white shrimp (Litopenaeus vannamei) larvae at early developmental stages. Biodiversitas 11 (2): 65-68.Terminal Restriction Fragment Length Polymorphism (T-RFLP) was used to monitor the dynamics of the bacterial communities associated with early developmental stages of white shrimp (Litopenaeus vannamei) larvae. Samples for analysis were egg, hatching nauplii, 24 hours old nauplii, and 48 hours old nauplii which were collected from one cycle of production at commercial hatchery. TRFLPresults indicated that the bacterial community associated with early stages of shrimp development might be transferred vertically from broodstock via egg. There was no significant difference between bacterial communities investigated, except the bacterial community of 48 hours old nauplii. Diversity analyses showed that the bacterial community of egg had the highest diversity and evenness, meanwhile the bacterial community of 48 hours old nauplii had the lowest diversity. Nine phylotypes were found at all stages with high abundance. Those TRFs were identified as Î³- proteobacteria, Î±-proteobacteria, and bacteroidetes group.Key words: Litopenaeus vannamei, bacterial community, T-RFLP